Realanalyzer HD: A real-time barbell tracking software for weightlifting - Sandau, I.; Jentsch, H.; Bunk, M. (EWF Scientific Magazine, 2019)
In this paper, we introduce the brand new barbell tracking software Realanalyzer HD for weightlifting that was developed at the IAT in Leipzig. We present some technical details of how to track the barbell on HD video and provide information regarding software evaluation, measured parameters and data interpretation.